2017
DOI: 10.3748/wjg.v23.i22.4102
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced liver injury in inflammatory bowel disease: 1-year prospective observational study

Abstract: AIMTo analyze 1-year liver injury burden in inflammatory bowel disease (IBD) patients.METHODSDuring a 6-mo inclusion period, consecutive IBD cases having a control visit at IBD center were included. Basic demographics, IBD phenotype and IBD treatment were recorded on entry. Aminotransferase (AT) activities of ALT, AST, ALP and gamma-glutamyl transpeptidase (GGT) were measured at baseline, 3 mo prior to study entry and prospectively every 3 mo for 1 year. Liver injury patterns were predefined as: Grade 1 in ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…Additionally, even though ANA can be used to diagnose AIH, positive ANA status before the initiation of therapy did not seem to place the patient at greater risk of developing DILI . Out of the patients that developed an AIH‐like picture from TNF‐α inhibitors, at least half of the patients required steroids while the other half recovered after stopping treatment …”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, even though ANA can be used to diagnose AIH, positive ANA status before the initiation of therapy did not seem to place the patient at greater risk of developing DILI . Out of the patients that developed an AIH‐like picture from TNF‐α inhibitors, at least half of the patients required steroids while the other half recovered after stopping treatment …”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 99%
“…Ghabril et al analyzed 34 cases of DILI related to TNF‐α inhibitors and found the most common presentation to be an autoimmune phenotype with improvement after drug withdrawal . In large retrospective studies, mild DILI (defined as ALT >2× ULN and/or ALP>2× ULN) was reported to have a 0.2%‐11% incidence, with the majority implicating infliximab . The absolute risk of DILI for patients that were started on infliximab was found in 1 of 120 users, 1 of 270 for adalimumab, and 1 of 430 for etancercept .…”
Section: Tumor Necrosis Factor Alpha Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major consideration given that the DILI Network has identified both thiopurine and biologic medications, specifically azathioprine and infliximab, as a Category A drug, indicating over 100 reported cases of liver toxicity [58]. A prospective cohort of treated IBD patients were followed with serial assessments of aminotransferase, bilirubin and alkaline phosphatase levels and most events were transients and did not require any significant change in IBD management [59]. A recent metaanalysis showed that immunomodulators and methotrexate did not result in an increase in NAFLD development; TNF alpha inhibitors had no association with rate of progression [59].…”
Section: Approach To Nafld In Ibdmentioning
confidence: 99%
“…A prospective cohort of treated IBD patients were followed with serial assessments of aminotransferase, bilirubin and alkaline phosphatase levels and most events were transients and did not require any significant change in IBD management [59]. A recent metaanalysis showed that immunomodulators and methotrexate did not result in an increase in NAFLD development; TNF alpha inhibitors had no association with rate of progression [59]. We do not recommend adjusting medical therapy in the presence of NAFLD/NASH unless drug-induced liver injury (DILI) is suspected.…”
Section: Approach To Nafld In Ibdmentioning
confidence: 99%